BENEFITING MORE OF PROJECT WORK IN A LARGE CLASS - Rohaniatul Makniyah (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2020)
This study sets out to discuss the implementation of Project-Based Learning (PjBL) in a large EFL secondary school setting. It aims at finding an alternative of how to implement PjBL for the purpose of taking more benefits of project works and analyzing the relevance of the implementation of which within an EFL secondary school large class. 41 learners of grade XI participated in the classroom action research. They are assigned to work in groups with a set of meaningful processes to do in every project work given within a period of time. The study found that project works can be maximized on the grounds that: (1) projects should be based on realistic and challenging tasks; (2) project should be structured within a set of meaningful processes; (3) project works are to be conducted collaboratively in groups to facilitate learners to learn in a large class.